Perceived barriers to effective implementation of public reporting of hospital performance data in Australia: a qualitative study - Rachel Canaway; Marie Bismark; David Dunt; Margaret Kelaher (BMC Health Services Research, 2017)
Abstract Background Public reporting of government funded (public) hospital performance data was mandated in Australia in 2011. Studies suggest some benefit associated with such public reporting, but also considerable scope to improve reporting systems. Methods In 2015, a purposive sample of 41 expert informants were interviewed, representing consumer, provider and purchasers perspectives across Australia’s public and private health sectors, to ascertain expert opinion on the utility and impact of public reporting of health service performance. Qualitative data was thematically analysed with a focus on reporting perceived strengths and barriers to public reporting of hospital performance data (PR). Results Many more weaknesses and barriers to PR were identified than strengths. Barriers were: conceptual (unclear objective, audience and reporting framework); systems-level (including lack of consumer choice, lack of consumer and clinician involvement, jurisdictional barriers, lack of mandate for private sector reporting); technical and resource related (including data complexity, lack of data relevance consistency, rigour); and socio-cultural (including provider resistance to public reporting, poor consumer health literacy, lack of consumer empowerment). Conclusions Perceptions of the Australian experience of PR highlight important issues in its implementation that can provide lessons for Australia and elsewhere. A considerable weakness of PR in Australia is that the public are often not considered its major audience, resulting in information ineffectually framed to meet the objective of PR informing consumer decision-making about treatment options. Greater alignment is needed between the primary objective of PR, its audience and audience needs; more than one system of PR might be necessary to meet different audience needs and objectives. Further research is required to assess objectively the potency of the barriers to PR suggested by our panel of informants.